Diabetic ketoacidosis and pancreatitis secondary to peg-asparaginase - Pires, Frederico Ribeiro; Souza, Camila Abreu de; Luiz, Murilo Brito; Kawahara, Selma Harue; Castro, Luiz Claudio Gonçalves de (Medicina (Ribeirao Preto), 2021)
Objectives: We present a rare case of diabetic ketoacidosis (DKA) and pancreatitis secondary to the use of PEG-asparaginase in a pediatric patient being treated for acute lymphoblastic leukemia (ALL) and draw attention to the signs that refer to these diagnoses. Case description: A female adolescent, aged 10 years and 11 months, undergoing treatment for ALL, used PEG-asparaginase for 6 days prior to admission. She was hospitalized due to severe hypotensive shock and was then referred to the intensive care unit. Initially, the clinical condition was interpreted as septic shock. However, detailed anamnesis and results of laboratory tests led to the diagnoses of DKA and pancreatitis; hence, appropriate interventions were initiated. She was discharged after 30 days without the need for insulin therapy but received pancreatic enzyme replacement therapy. Comments: Generally, diagnosing severely ill and leukopenic children with ALL is only attributed to sepsis, which is a priority diagnosis. However, in the group treated with PEG-asparaginase, the pediatric emergency specialist should consider differential reasoning in patients with DKA and pancreatitis, which can be quite difficult to assess initially. Alertness towards the differential diagnoses of septic shock, although rare, in the care of pediatric oncology patients, in addition to the correct and prompt identification of the condition and provision of appropriate management, directly correlates with treatment success and, in some situations, the improvement in patient’s survival.